Pengaruh Susu Kedelai terhadap Ekspresi Reseptor Estrogen-Β Uterus pada Masa Reproduksi Awal Rattus Norvegicus Betina: Effect of Soy Milk on Uterine Estrogen-Β Receptor Expression in the Early Reproductive Period of Female Rattus Norvegicus - Dinastiti, Vide Bahtera; Nurdiana, Nurdiana; Dwijayasa, Pande Made (Universitas Muhammadiyah Sidoarjo, 2019)
Receptors estrogen can also stimulated by other, namely by fitoestrogen. Fitoestrogen are the group of non steroid plants that have composition resembling the natural estrogen in the body. One of it is isoflavon, that can be binding with receptor estrogen, which affinity for RE-β is greater than RE-α and can make potential effect because receptors estrogen will blocked by isoflavon and cannot be occupied by estrogen.This compound can harm the endocrine system of the body because of the possible bad effects for reproductive function. Isoflavonoid is mostly found in soy. Soybean can be processed to soybean milk. The purpose of this study is demonstrate that administration of soy milk can affect the expression of RE-β uterus at the early reproductive period of female Rattus norvegicus. The method used is an experimental design post test control group design. The sample in this study is 24 Rattus norvegicus females. Then divided into four groups: one control group and three treatment groups were given soy milk each dose of 2.5 mg/kg/weight; 5mg/kg/weight; 10mg/kg/weight. The expression of RE-β uterus were measured by immunohistochemistry. Based on the analysis using ANOVA, was obtained p-value of 0.000, smaller than α = 0:05 (p <0.05). There is a significant influence on the administration of soy milk increase expression of RE-β and by LSD test obtained the results of differences from application of soy milk with different doses.